NAMA proposal on cattle production - International Center for Tropical Agriculture; Federación Colombiana de Ganaderos; Centro para la Investigación en Sistemas Sostenibles de Producción Agropecuaria; Nature Conservancy; World Resources Institute (2019)
NAMA Sustainable Bovine Livestock seeks to develop at a regional level the strategies proposed to reduce GHG emissions generated in livestock production In farms and in plants of sacrifice: increase the carbon sinks of the agro-ecosystems, by an environmental and productive organization at the regional level. Promote the conservation and/or restoration of natural ecosystems, encouraging sustainable productive landscapes through the harmonization of different public policy instruments.